Diversity of Production Techniques and Microbiology of African Cereal-Based Traditional Fermented Beverages - Felix Kwashie Madilo; Angela Parry-Hanson Kunadu; Kwaku Tano-Debrah; Firibu Kwesi Saalia; Unathi Kolanisi (Journal of Food Quality)
Traditional fermented beverages are culturally and socially accepted products for consumption, drinking, entertainment, customary practices, and for religious purposes. The purpose of this review was to identify some cereal-based fermented beverages and determine the differences in their production technologies. There are many unique regional variations in the preparation of each of the identified fermented beverages. They are prepared from raw materials such as maize, millet, rice, and sorghum. Majority of the fermented alcoholic beverages (binuburan, amba beer, sake, dolo, pito, and tchoukoutou) were produced using spontaneous fermentation and industrial fermentation (use of starter cultures) techniques. The various microbial communities associated with the traditional fermentation processes were dominated by Limosilactobacillus fermentum and Lactiplantibacillus plantarum for Lactic acid bacterial (LAB) species, Saccharomyces cerevisiae and Candida mycoderma for Saccharomyces and Candida species (yeasts), respectively; and Aspergillus aceti and Rhizopus stolonifer for Aspergillus and Rhizopus species (molds), respectively. Acetobacter, Pseudomonas, Klebsiella, Weissella, Achromobacter, Flavobacterium, Micrococcus, and Bacillus dominated other microbial genera. The involvement of lactic acid bacteria contributed to the safety and extension of the shelf life of the final products. Most of these beverages were found to be very rich in proteins, carbohydrates, calories, and B-group vitamins including thiamine, folic acid, riboflavin, and nicotinic acid. This article reviewed the available information, such as processing techniques of African traditional beverages, the raw materials used to producing them, and the microorganisms associated with the production processes.